2022
DOI: 10.3390/jof8050534
|View full text |Cite
|
Sign up to set email alerts
|

MAPK CcSakA of the HOG Pathway Is Involved in Stipe Elongation during Fruiting Body Development in Coprinopsis cinerea

Abstract: Mitogen-activated protein kinase (MAPK) pathways, such as the high-osmolarity glycerol mitogen-activated protein kinase (HOG) pathway, are evolutionarily conserved signaling modules responsible for transmitting environmental stress signals in eukaryotic organisms. Here, we identified the MAPK homologue in the HOG pathway of Coprinopsis cinerea, which was named CcSakA. Furthermore, during the development of the fruiting body, CcSakA was phosphorylated in the fast elongating apical part of the stipe, which meant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…We proposed that the expression of FfGS6 may be necessary for cell wall synthesis during the stipe elongation of F. filiformis ; however, a single elevation in cellular FfGS6 expression may lead to the excessive accumulation of β-1,6-glucan, thereby inhibiting the stipe elongation of F. filiformis . Since stipe elongation is one of the most complex biological process of fungi and could be regulated by multiple genes [ 42 , 43 ]. Needless to say, more studies are needed to verify this speculation.…”
Section: Discussionmentioning
confidence: 99%
“…We proposed that the expression of FfGS6 may be necessary for cell wall synthesis during the stipe elongation of F. filiformis ; however, a single elevation in cellular FfGS6 expression may lead to the excessive accumulation of β-1,6-glucan, thereby inhibiting the stipe elongation of F. filiformis . Since stipe elongation is one of the most complex biological process of fungi and could be regulated by multiple genes [ 42 , 43 ]. Needless to say, more studies are needed to verify this speculation.…”
Section: Discussionmentioning
confidence: 99%
“…Niu et al suggested that the stipe cell wall architecture varies in elongation and non-elongation regions, and the thickness of stipe cell wall is inversely proportional to the cell elongation rate [ 8 ]. It was also demonstrated that several proteins and signaling pathways could mediate stipe cell extension and are involved in stipe elongation [ 5 , 6 , 10 , 13 , 14 ]. However, the stipe is usually treated as an entire organization in most transcriptome studies [ 42 , 43 ], and the transcriptional landscape of stipe gradient elongation remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that glucanase, chitinase, and β-glucan-degrading enzymes associated with cell wall extension are involved in stipe elongation regulation [ 9 , 10 , 11 , 12 ]. In addition, the genes encoding septin protein Cc.Cdc3 and MAPK homologue CcSakA were also suggested to have important roles in controlling stipe elongation in C. cinerea [ 13 , 14 ]. In F. filiformis , the fruiting body at a length of 8.5 cm was defined as the elongation stage; in this stage, the apical 1.5 cm showed a fast elongation rate, the 1.5–3 cm section showed a slow elongate rate, and the region below 3 cm showed no further elongation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%